Next-generation biosensors for rapid detection of food contaminants: Advances in smartphone, CRISPR/Cas, aptamer, and AI-integrated sensing technologies - Rushikesh Deshmukh; Yogeshwari Hirikyathanahalli Vishweswaraiah; Rajashree Jena; Varij Nayan; Anuradha Bhardwaj; Diwas Pradhan; Raghu Hirikyathanahalli Vishweswaraiah (Next Research, 2026)

Epitope-targeted anti-internalin A and Internalin B antibodies enable lateral flow immune-chromatographic detection of Listeria monocytogenes in milk - Mariya Divanshi; Jitesh Tarak; Shreya Saha; Namita Narwal; Rashmi Hogarehalli Mallappa; Diwas Pradhan; Sachinandan De; Varij Nayan; Anuradha Bhardwaj; Arun Kumar Bhunia; Raghu Hirikyathanahalli Vishweswaraiah (International Dairy Journal, 2026)

miR-23 has been identified as a blood biomarker useful for estrus identification in Indian river buffaloes (Bubalus bubalis) - Naveen Swaroop Murikipudi; Pushpanjali Singh; Sunil Kumar; Chhama Singh; Rakshita Singh; Tanvi Bhatia; Prashant Kumar; Prashant Singh; Anuradha Bhardwaj; Sanjay Kumar; Sushil Kumar Phulia; Navneet Saxena; et al. (The Nucleus, 2026)

Genome-wide SNP mapping and selective sweep analysis in Indian equine breeds - Anuradha Bhardwaj; Jayakumar Sivalingam; Yash Pal; Varij Nayan; Mamta Chauhan; Sonali Soni; Saroj Panghal; Shiv Kumar Giri; Mohan Malayaperumal; Sarika Jaiswal; Mir Asif Iquebal; Vijay Kumar; et al. (The Nucleus, 2026)

Gold nanoparticles modulate the steroidogenic and apoptotic pathway in a buffalo granulosa cell model - Erica Lawai Lyngdoh; Varij Nayan; Monika Vashisht; Suman Kumari; Anuradha Bhardwaj; Tanvi Bhatia; Jasmer Dalal; Shikha Pawaria; Suneel Kumar Onteru; Poonam Sikka; Dheer Singh (Biotechnology Letters, 2020)

Molecular characterization, modeling, in silico analysis of equine pituitary gonadotropin alpha subunit and docking interaction studies with ganirelix - Anuradha Bhardwaj; Varij Nayan; Parvati Sharma; Sanjay Kumar; Yash Pal; Jitender Singh (In Silico Pharmacology, 2017)
Equine pituitary gonadotropins (eLH, eFSH, eCG) are heterodimeric glycoprotein hormones with alpha (α) and beta (β) subunits. It is responsible for maintenance of pregnancy in mares during early gestation and fairly valuable for inducing superovulation in animals other than equines. The alpha subunit is common, while beta subunit is species-specific in all glycoprotein hormones. In the present investigation, molecular cloning and in silico characterization including homology modeling and molecular docking analysis of the equine chorionic gonadotropin (eCG) alpha subunit was carried out for gaining structural and functional insights into the eCG alpha subunit and its possible interaction with ganirelix, a gonadotropin-releasing hormone (GnRH) antagonist. The equine chorionic gonadotropin (eCG) alpha subunit expressed in pituitary gland was selected, amplified from total RNA, cloned and sequenced. The in silico analyses were made for homology modelling, structural details, epitope identification and chromosomal localization. Molecular docking studies of eCG alpha were undertaken with a drug ganirelix which is used to control ovulation and has antagonistic activity against GnRH. The protein sequence corresponding to selected open reading frame (ORF) was 99–100% similar with domesticated horse, Przewalski’s horse, and 92–93% with Burchell’s zebra and donkey. Molecular docking studies revealed the possible interaction of eCG alpha with ganirelix. The possible drug-macromolecule interactions were visualized between eCG alpha and ganirelix. The study will provide structural insight into unique sites and an alternate route of gonadotropin suppression applicable to assisted reproductive technologies.

PAPP-A in Indian Water Buffalo (Bubalus bubalis) Ovary: Phylogeny, Expression, Hormonal Regulation, and Sequence Characterization - Varij Nayan; Anuradha Bhardwaj; Dheer Singh (Agricultural Research, 2013)